Nonlinear Dirichlet problems with double resonance - Aizicovici, Sergiu (2017)
We study a nonlinear Dirichlet problem driven by the sum of a $p-$Laplacian ($p>2$) and a Laplacian and which at $±∞$ is resonant with respect to the spectrum of $\left( -\triangle_{p},W_{0}^{1,p}\left( Ω\right) \right) $ and at zero is resonant with respect to the spectrum of $\left( -\triangle,H_{0}^{1}\left( Ω\right) \right) $ (double resonance). We prove two multiplicity theorems providing three and four nontrivial solutions respectivelly, all with sign information. Our approach uses critical point theory together with truncation and comparison techniques and Morse theory.